The process of losing - investigating the psychophysiological determinants of pacing and performance during head-to-head competition - Venhorst, A.; Micklewright, D.; Noakes, T. (Journal of Science and Cycling, 2017)
Introduction It is widely accepted that psychological factors can greatly influence human endurance and strength performance. However, little is known about the mechanisms that underpin facilitative and even more so debilitative cause-effect relationships between psychological factors and endurance performance during competition.[1] We recently developed a three-dimensional framework of centrally-regulated and goal-directed exercise behaviour emphasizing the important role of sensory-discriminatory, affective-motivational, and cognitive-evaluative processes underpinning observed pacing behaviour and performance.[2] The proposed framework offers a more sophisticated alternative to the traditional gestalt concept of perceived exertion in the investigation of the psychophysiological determinants of pacing and performance during prolonged endurance exercise. One aim of this experimental study was to examine the delineated contributions of the perceptual sensory, affective, and cognitive processes and their dynamic responses to respectively pulling ahead or falling behind a performance matched opponent.[3]